Journal of Shanghai Jiaotong University (Science) - Zheng, Hang.; SpringerLink (Online service) (Shanghai : Shanghai Jiaotong University Press : Imprint: Shanghai Jiaotong University Press, co-published with Springer.)
Journal of Shanghai Jiaotong University publishes research articles that reflect the latest achievements in basic theory and experimental studies in various engineering fields such as naval architecture and ocean engineering, material science, computer and communication engineering, electronic engineering and automation, and life sciences.
Keywords: Computer science; Architecture; Life sciences; Electrical engineering; Materials science; Electrical Engineering; Materials Science, general; Computer Science, general; Architecture, general; Life Sciences, general